Kontestasi antara pengetahuan modern dan tradisional dalam praktek pertolongan ibu hamil dan bayi di Kabupaten Gowa - Muhammad Syukur; Mario Mario (Seminar Nasional LP2M UNM, 2019)
Knowledge of labor practices that are owned by both shamans and midwife or medical personnel actors will certainly produce a power effect in the arena of labor. Instead the power possessed by each actor will give birth to knowledge in the arena of pregnant mother and baby help activities. This study aims to: 1) Analyze the contestation of modern knowledge possessed by midwives and local knowledge possessed by traditional birth attendants in the process of assisting pregnant women to the birth process in Gowa Regency. 2) Analyze the contestation of modern knowledge possessed by midwives and local knowledge possessed by traditional birth attendants in the process of care for postpartum mothers and infant care. Data collection is done using the method of in-depth interviews, observation and documentation. Data analysis is done through the process of data reduction, data presentation, and conclusion drawing. Checking the validity of the data is done in four ways, namely: credibility; transferability; dependability; confirmability. The results show that: 1) Contestation between modern knowledge and local knowledge in the practice of pregnant and childbirth assistance leads to a pattern of domination in which this pattern occurs in the arena of pregnancy, where modern knowledge of midwives dominates the traditional knowledge of shamans. 2) Contestation between modern and traditional knowledge in the practice of infant assistance shows a pattern of contestation of coexistence in which modern knowledge possessed by midwives and traditional knowledge possessed by traditional birth attendants are present together but have their respective parts without interfering with each other in the process of infant help